HAR BIR FUQAROGA DAVLAT HISOBIDAN ANIQ KASB-HUNARGA O’QITISH IMKONIYATINI YARATISH - Ashurova Gulbonu G’olibjon qizi (PEDAGOGS, 2024)
Annotation. This article analyzes the current system of public accounting and the possibilities of vocational training for citizens. The article shows how the Society of the state develops simpler and more citizens and increases its professional interests. It highlights the importance of vocational training for each citizen and how the state develops its applications for this transition. The article provides advice to citizens relating to recommendations on foreign and domestic programs for development and reform, educational systems, and legal challenges or financial provisions.